Diseño y realización de un programa de prácticas sobre comportamiento, adecuado al tema de etología - Álvarez Calvo, J. A.; García García, C.; Cubero Sánchez, Mª A. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
A program is being presented of experiments on animal behavior in which Fixed patterns of behd,ILIf sell us oine learning mechanism such as imprinting and operant conditioning are included. The aim is to expose the student (o the preparation and analysis of simple situations of experimental control which will permit the student to comprehend and appreciate the diverse factor wich together influence the apreance and maintenance of complex behavioral repertoires.